Susceptibility of different mice species to chemical induction of colorectal cancer by 1,2-dimethylhydrazine - Nourhan M. Abdelmaksoud; Ahmed I. Abulsoud; Tamer M. Abdelghany; Shereen Saeid Elshaer; Ahmed Samaha; Nadine W. Maurice; Sherine Maher Rizk; Mahmoud A. Senousy (Journal of the Egyptian National Cancer Institute)
Abstract Background Colorectal cancer (CRC) is a major public health concern. Animal models play a crucial role in understanding the disease pathology and development of effective treatment strategies. Chemically induced CRC represents a cornerstone in animal model development; however, due to the presence of different animal species with different genetic backgrounds, it becomes mandatory to study the susceptibility of different mice species to CRC induction by different chemical entities such as 1,2-dimethylhydrazine (DMH). This study aimed to investigate the induction receptivity of two commonly used mice species, C57BL/6 and BALB/c, to DMH-induced CRC. Methods Both mice species were exposed to weekly intraperitoneal injections of DMH at a dose of 20 mg/kg body weight for 15 consecutive weeks. The response to DMH was evaluated by monitoring body weight gain, daily food intake, and gastrointestinal symptoms. At the end of exposure, histopathology of distal colon dissected from both species was analyzed. Results Results revealed that C57BL/6 had a higher response to DMH compared to BALB/c. A significant decrease in body weight gain concomitant with severe diarrhea was observed in C57BL/6 receiving DMH compared to their controls, without any difference in food intake. Histopathology of distal colon revealed aberrant crypt foci and loss of goblet cells in DMH-exposed C57BL/6 mice. On the other hand, BALB/c mice displayed a normal and intact colon, with a normal weight gain pattern, and without any gastrointestinal symptoms. Conclusion In conclusion, C57BL/6 has a higher susceptibility toward chemical induction to CRC; therefore, it can be used to study CRC pathogenesis, prevention, and treatment.